The effects of spiradoline (U-62066E), a kappa-opioid receptor agonist, on neuroendocrine function in man. - Ur, E; Wright, D; Bouloux, P; Grossman, A (1997)
1. Opioid drugs act on specific receptors which are principally classified into mu, delta and kappa subtypes. Spiradoline (U-62066E) is a kappa-selective agent which has been shown to possess potent anti-nociceptive effects but does not show cross tolerance with morphine. 2. We have assessed the neuroendocrine effects of spiradoline in healthy volunteers with two doses (1.6 and 4.0 micrograms kg-1, i.m.) of the compound. Six male non-smokers aged 19-27 years were studied by use of a randomized, double-blind three-limb placebo-controlled cross-over design. Blood was taken from an in-dwelling venous cannula basally and at 15 min intervals for 2 h for determination of serum cortisol, prolactin, growth hormone (GH) and catecholamines. 3. Psychological function was assessed by the Stanford Sleepiness Scale (SSS) and the Addiction Research Centre Inventory (ARCI) administered before the medication and at 35 min, 1 h 25 min and 2 h afterwards. Cardiovascular variables were recorded at 10 min intervals. Results were analysed by analysis of variance. 4. Spiradoline showed a significant (P < 0.05) dose-dependent increase in free water clearance, as predicted for a kappa-opioid agonist. It also caused a dose-dependent stimulation of prolactin, (increment over baseline for higher dose 214%), GH (433%) and cortisol (215%) release (P < 0.05). There were no significant drug-related changes in plasma catecholamines, blood pressure, pulse or psychological variables. 5. We have therefore confirmed that kappa-opioids increase free-water clearance and may participate in the stimulation of prolactin and GH release. In contrast to mu and delta-opioid agonists, this novel kappa-agonist stimulates cortisol release in man.